Lead-Time Variability and Single-Source Dependence as Continuity Risks in an Aerospace Metallic Raw-Material Supply Network - Eko Taufik Sutisna; Liane Okdinawati (Publikasi Indonesia, 2026)
Aerospace manufacturers that source flight-critical metallic raw materials over long distances are widely assumed to face continuity risk because of that distance. This paper tests that assumption through an embedded single-case study of a Tier-1 Indonesian manufacturer (pseudonymized as PT VC Aero Bandung) that procures European forged billets and forgings for Airbus A320 flight-control components. The study followed a quantitatively dominant, explanatory-sequential mixed-methods design: it draws on the firm’s supplier and origin master data, 692 inbound shipment records (2023–2026), and safety-stock policy data, triangulated with secondary logistics and lead-time benchmarks, and then interprets that evidence through three semi-structured expert interviews. Three procedures are combined to locate where continuity risk resides, supply-network mapping, lead-time and variability analysis by sourcing region, and single-source concentration analysis across the part portfolio. Three findings emerge. First, the binding constraint is not shipping distance but upstream forging and melt capacity: air transit is short and stable across origins (mean 4.4 days), and even by sea the logistics leg is a minority of the 42-week order-to-delivery lead time, so geography enters mainly through the freight-mode decision. Second, the core vulnerability is lead-time variability (±8 weeks), not length: actual safety stock of three to five weeks sits far below the roughly eighteen weeks the variability would require to absorb. Third, all 124 metallic part numbers are single-sourced (close to 100 percent of spend), with one billet supplier (T UK) alone at about 64 percent, and the dependence falls hardest on the NADCAP-qualified flight-control forgings.